Model Simulations of a Mesocosm Experiment Investigating the Response of a Low Nutrient Low Chlorophyll (LNLC) Marine Ecosystem to Atmospheric Deposition Events - Tsiaras, Kostas P.; Christodoulaki, Sylvia; Petihakis, George; Frangoulis, Constantin; Triantafyllou, George (Frontiers in Marine Science, 2017)
Atmospheric deposition of nitrogen and phosphorus represents an important source of nutrients, enhancing the marine productivity in oligotrophic areas, e.g. the Mediterranean. A comprehensive biogeochemical model (ERSEM) was setup and customized to simulate a mesocosm experiment, where dissolved inorganic nitrogen and phosphorus by means of atmospheric dust (single addition/SA and repetitive addition/RA in three successive doses) was added in controlled tanks and compared with a control (blank), all with Cretan Sea (Eastern Mediterranean) water. Observations on almost all components of the pelagic ecosystem in a ten-day period allowed investigating the effect of atmospheric deposition and the pathways of the added nutrients. The model was able to reasonably capture the observed variability of different ecosystem components and reproduce the main features of the experiment. An enhancement of primary production and phytoplankton biomass with added nutrients was simulated, in agreement with observations. A significant increase of bacterial production was also reproduced, while the model underestimated the observed increase and variability in bacterial biomass, but this deviation could be partly removed considering a lower carbon conversion factor from cell abundance data. A slightly stronger overall response was simulated with the single dust addition, compared to the repetitive that showed a few days delay. The simulated carbon pathways indicated that nutrient additions did not modify the microbial food web structure, but just increased its trophic status. Changes in model assumptions and parameter set that were necessary to reproduce the observed variability in the mesocosm experiment were discussed through a series of sensitivity simulations. Bacterial production was assumed to be mostly affected by the in situ produced labile organic matter, while it was further stimulated by the addition of inorganic nutrients, adopting a function of external nutrient concentrations for bacteria nutrient limitation. The effective increase in phytoplankton nutrient uptake rate was necessary, in order to reproduce the observed primary production, under such low nutrient concentrations, as also the increase of the grazers growth rate. The model was thus tuned to better work under very low nutrient concentrations, such as those found in the Eastern Mediterranean.